CONSCIOUSNESS INCARNATE: CONCEPT OF BODY IN MERLEAU-PONTY AND RAMANUJA: . - Edattukaran, Wilson (Journal of Dharma, 2002)
The birth of any philosophy is from man's becoming conscious of his lived experiences. If philosophy is ultimately rooted in experience and consciousness, it evolves in particular contexts and cultures of peoples, always attempting at articulating the manifold layers of man's 'Lebenswelt', Philosophers and their philosophies are invariable products of the worlds they lived in, thoughts they shared and traditions they inherited. Maurice MerleauPonty (1908-1961) and Ramanuja (c. 10 17-1137), representing two great philosophical traditions are two philosophers who made unique contributions towards a creative and convergent thinking focussing on the body as an Incarnate Consciousness